Penyelesaian Klaim Asuransi Jiwa Menurut Klaim Ex-Gratia - Imadasari, Rheza (Unnes Law Journal: Jurnal Hukum Universitas Negeri Semarang, 2013)
Life insurance companies offer protection to human life that aims to provide security and comfort as well as provide the right solution to overcome the risks. Ease in settlement of insurance claims also be featured each company. The purpose of this study was to determine the settlement of insurance claims according to claim AIA Ex-Gratia in Semarang and Financial Agency to determine the basis for determining the amount of compensation on claims administration Ex-Gratia in AIA Financial Agency Semarang. The approach used in this study is a socio-juridical. Data collection techniques are interviews with the validity of the technique of triangulation. The results showed that the AIA Financial Agency Semarang still provide compensation to the heirs, although conditions in the settlement of claims less fulfilled and not guaranteed in the policy. Granting compensation is based on the good faith of the company in light of the internal SOP where companies have to maintain a good reputation in doing business in the area of ??insurance. Conclusions from this research that the insurance companies are still giving money compensation to the heirs of 50% of the total premi paid by the insured during his lifetime as well as the good faith of the insurance company to maintain customer confidence.